A pizza the size of the sun : poems - Prelutsky, Jack.; Stevenson, James, 1929-2017 (New York, N.Y. : Scholastic, 1997)
A collection of humorous poetry on a variety of topics.
Includes indexes.
Keywords: Children's poetry, American; American poetry; Humorous poetry